Trade protection and tax evasion: Evidence from Kenya, Mauritius, and Nigeria - Bouët, Antoine; Roy, Devesh (International Food Policy Research Institute, 2008)
We examine the effect of trade protection rates on evasion in three African countries: Kenya, Mauritius, and Nigeria. In capturing the effect of trade protection on tariff evasion, we use a much improved measure of trade protection from MacMAP 2001 and 2004. For two of these countries, the MacMAP data set allows the novelty of using variation in trade protection across product, time, and trading partners, leading to significantly refined estimates of evasion elasticity relative to existing studies on tariff evasion. We find a positive elasticity of evasion with respect to tariffs in all three countries. Further, our results match the rankings of countries in terms of institutional quality. Greater responsiveness of evasion to the level of tariffs is established in Nigeria (comparatively weak institutional quality) vis-à-vis Kenya, and in Kenya vis-à-vis Mauritius (comparatively good institutional quality). This pattern is preserved even when focusing on the same set of trading partners and the same set of imported products for the three countries. This result is robust to controlling for protection on related products (that create incentives/opportunities for evasion) and also for degree of differentiation of the product in question (characteristics that determine the ease of detection of evasion).